2020
DOI: 10.17712/nsj.2020.3.20190093
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum index correlates with brain volumetry and disability in multiple sclerosis patients

Abstract: Objectives:To analyze the correlation between corpus callosum index )CCI(, brain volumetry, and disability in multiple sclerosis )MS( patients. The brain volumetry consists of the corpus callosum, cortical gray matter, subcortical gray matter, and white matter volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In our reproducibility analysis, we compared the normalized CC area that was obtained from segmentations performed on manually The CC is a promising marker for several neurodegenerative diseases such as Alzheimer's disease, 30 Parkinson's disease, 31 amyotrophic lateral sclerosis, 32 and particularly MS. 33 Its significance in MS is intimately tied to the CC being a large white matter structure in a disease that predominantly affects myelin. Several studies have shown that the extent of damage to the CC significantly correlates to both physical and cognitive disabilities, 7,27,34 and that the CC is a predictor of cognitive disability 8.5 years later. 5 Our observations corroborate this notion, showing significant correlations with both EDSS and SDMT at both baseline and follow-up on average 6-7 years later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our reproducibility analysis, we compared the normalized CC area that was obtained from segmentations performed on manually The CC is a promising marker for several neurodegenerative diseases such as Alzheimer's disease, 30 Parkinson's disease, 31 amyotrophic lateral sclerosis, 32 and particularly MS. 33 Its significance in MS is intimately tied to the CC being a large white matter structure in a disease that predominantly affects myelin. Several studies have shown that the extent of damage to the CC significantly correlates to both physical and cognitive disabilities, 7,27,34 and that the CC is a predictor of cognitive disability 8.5 years later. 5 Our observations corroborate this notion, showing significant correlations with both EDSS and SDMT at both baseline and follow-up on average 6-7 years later.…”
Section: Discussionmentioning
confidence: 99%
“…The CC is a promising marker for several neurodegenerative diseases such as Alzheimer's disease, 30 Parkinson's disease, 31 amyotrophic lateral sclerosis, 32 and particularly MS. 33 Its significance in MS is intimately tied to the CC being a large white matter structure in a disease that predominantly affects myelin. Several studies have shown that the extent of damage to the CC significantly correlates to both physical and cognitive disabilities, 7 , 27 , 34 and that the CC is a predictor of cognitive disability 8.5 years later. 5 Our observations corroborate this notion, showing significant correlations with both EDSS and SDMT at both baseline and follow‐up on average 6‐7 years later.…”
Section: Discussionmentioning
confidence: 99%
“…All ROIs were visually examined by one rater (EE) for registration errors with respect to the subject's anatomical MR images. Five of 16 PwMS had errors caused by inaccurate registration, reflected as an overestimation of the superior border of the CC body due to drastic differences in CC morphology in MS patients, in whom callosal atrophy is commonly reported 31 . All misaligned ROIs were manually edited to better fit the anatomy (EE).…”
Section: Methodsmentioning
confidence: 99%
“…Five of 16 PwMS had errors caused by inaccurate registration, reflected as an overestimation of the superior border of the CC body due to drastic differences in CC morphology in MS patients, in whom callosal atrophy is commonly reported. 31 All misaligned ROIs were manually edited to better fit the anatomy (EE). Images (T 1 -weighted, FLAIR, MWF, and geomT 2IEW ) from a representative participant are shown in Figure 2.…”
Section: Mwi Acquisition and Postprocessingmentioning
confidence: 99%
“…It was revealed that this might indicate cortical-spinal atrophy and lesion burden. Correlation has also been shown between the structural measurements of the CC and the volumetric properties of the brain (8,9). It was also determined that CC injury is associated with cognitive impairment in MS patients and may be a clinically significant marker of cognitive impairment (10)(11)(12).…”
Section: Introductionmentioning
confidence: 96%